Polish National Cittaslow Network: assessment of cities’ membership in the network - Wierzbicka, Wioletta (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: The Polish National Cittaslow Network associates 31 members and is the second most biggest national network of slow cities in the world. The network is developing very dynamically. Therefore, it is important to observe this relatively new and not fully recognized process of implementing the slow city model in Polish cities, and to assess the effects of cities’ membership in this network. Aim: The aim of the study was to evaluate effects of the membership of cities in the Polish National Cittaslow Network. The effects were assessed on the basis of a comparative analysis of the results of certification carried out before a city accessed the network with the results of recertification, carried out 5 years into its membership. A diagnostic survey method was also used in the study. Results: The research shows that already in the first five years of the membership in the network, the cities have undertaken many activities to enhance their appeal as a tourist destination, promote local products and protect the historic and cultural heritage. The cities have completed many revitalisation projects. New tourist trails, bicycle paths and recreational areas have been created. Undoubted, the membership in the Cittaslow network has generated many benefits to the cities. This is reflected by the higher degree of the fulfilment of the certification criteria by all cities. This is also confirmed by the results of a diagnostic survey conducted among the mayors of member cities.